Needlestick Injuries in Dentistry - Gupta, N; Tak, J (Kathmandu University Medical Journal, 2012)
Needlestick injuries and other sharps-related injuries which expose health care professionals to bloodborne pathogens continue to be an important public health concern. Dentists are at increased risk of exposure to bloodborne pathogens, including Hepatitis B, Hepatitis C, and HIV. This article presents comprehensive information on Needlestick injuries (NSI), post exposure prophylaxis, precautions and suggestions for prevention of NSI in dentistry. Dentists should remember and apply many precautions to prevent the broad spectrum of sharps and splash injuries that could occur during the delivery of dental care. DOI: http://dx.doi.org/10.3126/kumj.v9i3.6307 Kathmandu Univ Med J 2011;9(3):208-12